1966
DOI: 10.1152/ajplegacy.1966.210.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Response of capacity and resistance vessels of dog's limb to sympathetic nerve stimulation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1967
1967
1983
1983

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…Edis, Donald & Shepherd (1970) reported a reduction in heart rate following inflation of balloons in the pulmonary vein-atrial junction, particularly when the initial heart rate was high. In the present experiments we observed that an increase in impulse activity occurred in cardiac sympathetic fibres even when the Cloninger & Green (1955), Browse, Lorenz & Shepherd (1966) and Donald & Ferguson (1970). On the other hand, the results of Edis et al (1970), who observed a decrease in systemic vascular resistance following distension of the pulmonary veinatrial junctions with large balloons, are clearly different from the present results.…”
Section: Discussioncontrasting
confidence: 99%
“…Edis, Donald & Shepherd (1970) reported a reduction in heart rate following inflation of balloons in the pulmonary vein-atrial junction, particularly when the initial heart rate was high. In the present experiments we observed that an increase in impulse activity occurred in cardiac sympathetic fibres even when the Cloninger & Green (1955), Browse, Lorenz & Shepherd (1966) and Donald & Ferguson (1970). On the other hand, the results of Edis et al (1970), who observed a decrease in systemic vascular resistance following distension of the pulmonary veinatrial junctions with large balloons, are clearly different from the present results.…”
Section: Discussioncontrasting
confidence: 99%
“…Another explanation may be the occurrence of a local feedback inhibition by norepinephrine on alpha presynaptic receptors (20,21,25). The frequency of stimulation that produced the maximum catecholamine level in coronary sinus blood and the maximum intensity of cardiac responses was 10 Hz, a finding which is in agreement with previous reports on the optimum frequency of sympathetic nerve stimulation (26)(27)(28)(29).…”
Section: Figuresupporting
confidence: 90%
“…Figure 2 is typical of the responses of the vessels in the occluded hind limb to sympathetic nerve stimulation. The arterial pressure rose rapidly, almost a square wave, the venous pressure somewhat more slowly; these changes have been fully documented elsewhere (Browse, Lorenz & Shepherd, 1966). The lymphatic pressure increased slowly, the rise beginning after 5-10 sec and reaching its asymptote in lf-2 min.…”
Section: Methodsmentioning
confidence: 55%
“…It has been shown in both the dog (Browse, Lorenz & Shepherd, 1966; and man (Samueloff et al 1966) that the venous volume remains constant below a suprasystolic occluding cuff. It is reasonable to assume that this is also true of lymphatic volume for these vessels do not communicate directly with either artery or vein.…”
Section: Discussionmentioning
confidence: 98%